The SWI/SNF chromatin-remodeling subunit DPF2 regulates macrophage inflammation in intestinal injury via the CACNA1D-mediated MAPK pathway - Mintao Ji; Haisheng Liang; Shuai Dong; Yuhan Guo; Yiping Lin; Hong Zhang; Yuhong Wang; Zhe Lei; Xiaoya Xu; Yinyin Shu; Zhisen Zhang; Xiaoni Jin; et al. (Proceedings of the National Academy of Sciences, 2025)
The immune system plays a pivotal role in pathogenesis of intestinal injury and subsequent regenerative processes, particularly macrophages, orchestrate the inflammatory response and tissue repair. Here, we identified that loss of double PHD fingers 2 (DPF2) enhances intestinal regeneration and reduces inflammation. Using a combination of mouse genetics, single cell RNA sequencing, and spatial transcriptomics, we found that Dpf2 loss in macrophage modulates inflammatory polarization, thus protecting against intestinal injury. Mechanistically, Dpf2 deficiency leads to loss of H3K27ac and H3K4me1 marks at Cacna1d enhancer, impairing Cacna1d messenger RNA (mRNA) expression and reducing intracellular calcium. Consequently, loss of Dpf2 attenuates mitogen-activated protein kinases signaling activity, promoting an anti-inflammatory macrophage polarization. Finally, through analysis of clinical inflammatory bowel disease (IBD) single cell RNA and spatial transcriptome data, patient-derived organoids and clinical samples, we validated a positive correlation between DPF2, CACNA1D, and intestinal inflammation. Our findings establish an essential role for DPF2 in facilitating CACNA1D expression in macrophages to regulate intestinal inflammation and regeneration.